Aryl- and Heteroaryl Substituted Tandospirones as Possible Antidepressant Drugs - Gunkara, Omer Tahir; Kulu, Irem; Ocal, Nuket (BENTHAM SCIENCE PUBL LTD, 2015)
Nowadays, heterocyclic compounds which have a nitrogen atom on the structure, such as pharmacological products, pesticides and antimicrobials can be demonstrated by biologically-active groups that serve the pharmaceutical industry and they are still important in this field. Various cyclization reactions form the basis of the literature on the syntheses of heterocyclic compounds. N-Arylpiperazines are a class of heterocyclic compounds that play an important role in organic synthesis and are generally found as fragments in receptor ligands and natural products. They have been used extensively as reactive species for building chemical diversity. Arylpiperazines are also found in many pharmacologically-active molecules. Our research group has published numerous papers over the last two years on the synthesis of potentially bioactive tandospirone analogues which have a piperazine group by reductive Heck reactions. We also reported some important isoxazoline derivatives by 1,3-dipolar cycloadditions. Our work continued with potentially pharmacologically-active tandospirone analogues which have an exo-ring in the tricyclic system with an oxygen bridge and containing a 3-(trifluoromethyl) phenyl and 2,3-dichlorophenyl group on the aromatic ring.
Keywords: Antidepressant drugs; arylpiperazines; C-C coupling; 1,3-dipolar cycloadditions; Heck reaction; heterocycles; hydroarylation; tandospirone; DOMINO-HECK REACTIONS; BRIDGED PERHYDROISOINDOLE DERIVATIVES; EXPECTED ANXIOLYTIC ACTIVITY; DOPAMINE D3 RECEPTOR; TRICYCLIC IMIDES; UNSATURATED DICARBOXIMIDES; ISOXAZOLINE DERIVATIVES; CYCLOADDITION REACTIONS; 5-HT1A AGONIST; ANALOGS; Pharmacology & Pharmacy